Extended‐Release Oral Milrinone for the Treatment of Heart Failure With Preserved Ejection Fraction. Issue 13 (7th July 2020) - Nanayakkara, Shane; Byrne, Melissa; Mak, Vivian; Carter, Kaye; Dean, Eliza; Kaye, David M.
Abstract : Background: Heart failure with preserved ejection fraction (HFpEF) is an increasingly prevalent form of heart failure, representing half of the total burden of heart failure. We hypothesised that modulation of the phosphodiesterase type 3/cyclic AMP using a novel oral formulation of milrinone might exert favorable effects HFpEF via pulmonary and systemic vasodilation and enhancement of ventricular relaxation. We assessed the safety and efficacy of oral milrinone on quality of life and functional outcomes in patients with HFpEF. Methods and Results: The MilHFPEF (Extended Release Oral Milrinone for the Treatment of Heart Failure With Preserved Ejection Fraction) study was a randomized, double‐blind, placebo‐controlled pilot study in 23 patients with symptomatic HFpEF. Efficacy end points included changes from baseline in Kansas City Cardiomyopathy Questionnaire summary score and 6‐minute walk distance. The primary safety end point was the development of clinically significant arrhythmia. The Kansas City Cardiomyopathy Questionnaire score improved significantly in milrinone‐treated patients compared with placebo (+10±13 versus −3±15; P =0.046). Six‐minute walk distance also tended to improve in the treatment group compared with placebo (+22 [−8 to 49] versus −47 [−97 to 12]; P =0.092). Heart rate (−1±5 versus −2±9 bpm; P =0.9) and systolic blood pressure (−3±18 versus +1±12 mm Hg; P =0.57) were unchanged. Early filling velocity/early mitral annular velocity (−0.3±3.0 versus −1.9±4.8; P =0.38) was unchanged. One patient in the placebo arm was hospitalized for heart failure. Holter monitoring did not demonstrate evidence of a proarrhythmic effect of milrinone. Conclusions: In this novel pilot study, extended release oral milrinone was well tolerated and associated with improved quality of life in patients with HFpEF. Further longer‐term studies are warranted to establish the role of this therapeutic approach in HFpEF. Registration: URL: https://www.anzctr.org.au/ ; Unique identifier: ACTRN12616000619448.